A Systematic Literature Review: Dinamika Voice Behavior pada Karyawan dan Organisasi - Cantika Deana Putri; Yunita Faela Nisa; Abdul Mujib (Jurnal Riset Akuntansi, 2026)
Organizational sustainability requires highly engaged employees throughout the organization. This can be achieved by encouraging employees to engage in voice behavior. This research aims to examine the dynamics of voice behavior in an organizational context through the Systematic Literature Review (SLR) method with the PRISMA approach. Literature was collected from Google Scholar, JSTOR, Taylor & Francis, APA PsycNet, and Garuda databases with keywords related to employee voice behavior. From the initial 21,198 articles (2021-2025), 11 articles were selected based on inclusion criteria and quality assessment. The results showed that voice behavior is influenced by various factors consisting of external factors and internal factors. This study confirms the importance of a holistic approach to employee voice behavior to encourage innovation in organizations so that it remains optimal and sustainable.